ANALISIS PENGEMBANGAN USAHA MELALUI INOVASI PRODUK PADA UMKM KERAJINAN MONEL DI SENTRA KERAJINAN MONEL KRIYAN JEPARA (Studi pada UMKM di Sentra Kerajinan Monel Kriyan Jepara) - Muhammad Rizky Alamsyah; Rodhiyah Rodhiyah (Universitas Diponegoro, 2019)
Kriyan monel craft is one of the superior products in Jepara Regency. Therefore, the development of monel Kriyan MSMEs is important, including through Innovation. The problems that occur in monel craft are facing competition from foreign countries, especially from China. The objectives of this study were: 1) to know the condition of MSMEs in the center of Kriyan monel craft. 2) Knowing the business development of SME craft monel in Kriyan Kalinyamatan Jepara village. 3) Knowing the innovations made on monel Kriyan craft products, 4) Knowing business development and innovation in monel Kriyan Kalinyamatan Jepara craft products. The method of this research is qualitative descriptive. The research locus was conducted at the Kriyan village monel craft center, Jepara. The subjects of this study are producers or craftsmen, as well as monel traders. The data in this study were obtained from MSMEs, monel craftsmen and traders. The results of research in the field are known to 59 SMEs who are in the center of Kriyan monel craft. Of these, there are 44 small MSMEs or around 75 percent, medium MSMEs totaling 8 MSMEs or 13 percent and large MSMEs as many as 7 MSMEs or 12 percent. The conclusion is that based on the number of workers owned by most MSMEs, the monel craft at the Kriyan monel craft center is a small MSME status. Conclusion: Large MSMEs are more innovative than small MSMEs due to limited human resources. It is necessary to innovate product development through product design innovation, equipment innovation, marketing innovation and innovation of small and medium MSME production facilities in order to further increase sales and competitiveness until finally business development occurs, the advice given to MSME players is internal consolidation through strengthening organization or association. Then increase the capacity of business people and build communication and cooperation with relevant stakeholders to find solutions to develop monel craft business.